Towards Sustainable e-Waste Practices: A Value-Belief-Norm Analysis of Mobile Phone Disposal in Ghana - Alina Iskander; Vanessa Heinrich; Magnus Fröhling (Sustainable Development, 2025)
Electronic waste (e-waste) from mobile phones is a growing concern in resource-constrained contexts, where limited infrastructure and regulatory enforcement promote reliance on informal systems. In Ghana, a rapidly expanding digital market, e-waste accumulation poses significant environmental and social challenges. This study investigates the behavioral drivers behind mobile phone disposal using the Value-Belief-Norm (VBN) theory and aims to extend the VBN framework by applying it to the context of e-waste management in the developing Ghanaian economy. Data collected from 110 participants across Ghana were analyzed with partial least squares structural equation modeling. Findings reveal that while a pro-environmental worldview does not directly heighten awareness of improper disposal consequences, increased awareness enhances responsibility attribution, which strongly shapes personal norms and drives policy support and private-sphere actions. Notably, materialistic values exhibit a negative effect, suggesting that economic and status-related factors may override prosocial motivations. Promoting sustainable disposal practices requires strategies that align economic incentives with enhanced personal responsibility and social norms.
Keywords: 330; circular economy; consumer behavior; electronic waste management; environmental psychology; informal sector